Light quenching of pyridine2 fluorescence with time-delayed pulses - Gryczynski, Ignacy (Biophys Chem, 1997)
We describe the effects of time-delayed long-wavelength pulses on the intensity and anisotropy decays of pyridine2. The sample was exposed to a continuous train of 360 nm excitation pulses and time-delayed 720 nm pulses. The long-wavelength pulses, which overlapped the emission spectrum of pyridine2, resulted in a spatially localized decrease in intensity at the point of beam overlap. The time-delayed quenching pulses caused a stepwise decrease in the intensity and anisotropy decays, as seen by oscillations in the frequency-domain data. The time-resolved anisotropy was shown to decrease below zero (−0.2) following the vertically polarized quenching pulse. The extent of light quenching depended on the time delay between the excitation and quenching pulses, and can be used to measure the decay time. Light quenching and/or multipulse methods may provide a new class of experiments for fluorescence spectroscopy and imaging.